Asymmetric septal edema masking as hypertrophy in an infant with COVID-19 myocarditis. (March 2022) - Edwards, Jonathan J.; Harris, Matthew A.; Toib, Amir; Burstein, Danielle S.; Rossano, Joseph W.
Abstract: Cardiac disease in pediatric patients due to coronavirus SARS-CoV-2 disease (COVID-19) includes myocarditis and multisystem inflammatory syndrome, both of which can present with a broad range in severity. Here we describe an infant with COVID-19 causing fulminant myocarditis with inotrope-resistant acute heart failure requiring extracorporeal membrane oxygenation. The patient demonstrated an atypical finding of localized septal thickening suggestive of hypertrophic cardiomyopathy, but the diagnosis of myocarditis was confirmed by cardiac MRI. Serial echocardiography illustrated complete resolution of septal hypertrophy and normalized cardiac function. The current report highlights the potential severity of COVID-19 associated myocarditis, the potential for recovery, and the utility of cardiac MRI in confirming the mechanism. Highlights: COVID-19 can cause acute myocarditis or multisystem inflammatory syndrome with a broad range of severity. This report describes an infant with COVID-19 fulminant myocarditis requiring extracorporeal membrane oxygenation. We also highlight how cardiac MRI can differentiate severe septal thickening of myocarditis from myocardial hypertrophy.